The effect of digestible protein to digestible energy ratio and choline supplementation on growth, hematological parameters, liver steatosis and size-sorting stress response in Nile tilapia under field condition - Fernandes Junior, Ademir Calvo [UNESP]; Pucci Figueiredo de Carvalho, Pedro Luiz [UNESP]; Pezzato, Luiz Edivaldo [UNESP]; Albers Koch, Joao Fernando [UNESP]; Teixeira, Caroline Pelegrina [UNESP]; Cintra, Felipe Tenorio [UNESP]; Damasceno, Flavia Motta [UNESP]; Amorin, Renee Laufer [UNESP]; Padovani, Carlos Roberto [UNESP]; Barros, Margarida Maria [UNESP] (Elsevier B.V., 2016)
This study evaluated growth performance, hematological parameters, histological liver analysis, and production costs of Nile tilapia fed increasing levels of digestible protein, digestible energy, and choline. Twelve thousand Nile tilapia (148 +/- 6.7 g) were randomly distributed into 80 1 m(3) net cages, in a 5 x 2 x 2 factorial design with five digestible protein (DP) levels (24, 26, 28, 30, and 32% DP), two digestible energy (DE) levels (13.4 and 14.65 MJ DE kg(-1) diet), and two choline levels (0.0 and 1000 mg kg(-1) diet), with four replicates per treatment. Fish fed the higher energy level showed a sparing effect of protein; the higher protein level determined the highest fillet yield. Fish fed diets with 24% DP showed the highest liver lipid, and independently of treatment-all analyzed fish showed hepatocyte degeneration. The best benefit cost ratio for whole fish production was achieved with 28% DP/13A MJ DE kg(-1), and for fillet production with 30% DP/13.4 MJ DE kg(-1). The results of the hematological assay showed alterations in red blood cells, mean corpuscular volume, albumin, Albumin:Globulin ratio, and glucose after size-sorting stress. Overall, these results indicate a lower resistance to stress, mainly for fish fed with no choline and oil supplementation. In this study we determined that the best performance was achieved with DP:DE ratios of 21.45 g MI-1 (28.74% DP/13.4 MI DE kg-1) and 18.60 g MI-1 (2725% DP/14.65 MJ DE kg-1). The highest fillet yield was obtained with 30% DP, regardless of the dietary energetic level. Sustained homeostasis was observed in this setting, and even though size-sorting stress altered some hematological parameters, they were still within the range recognized as healthy. Choline was not effective in protecting the liver against hepatic steatosis, but was able to buffer some of the negative effects of stress under these rearing conditions. Statement of Relevance: This research has been approved by the Ethics Committee of our Institution. Our team has been working with nutrition and fish health since 2000. According to the NRC (2011), only a few studies have been conducted to estimate the dietary nutrient requirements of farmed fish under intensive culture conditions. Moreover, a number of factors may affect the dietary and nutritional requirements of fish differentially in the laboratory and under intensive culture. For example, climatic conditions may fluctuate widely in the field, directly affecting physiological responses, hence nutritional requirements. Similarly, fish densities are much higher under intensive farming. Establishing the appropriate nutritional requirements in these settings must also consider the trade-off between growth performance and production costs. Based on this, we investigated the effect of different levels of digestible protein and digestible energy on growth performance and hematological responses of the Nile tilapia in a commercial fish farm in Brazil, where fish farmers are known to use diets with excessive levels of crude protein throughout fish culture and hepatic steatosis is often reported. Therefore, we also investigated the potential hepatic protective effect of choline against such conditions. Finally, we analyzed the health status, as measured by hematological parameters, of fish subjected to handling-induced stress procedures that are usual on fish farms. (C) 2016 ElsevierB.V. All rights reserved.
Keywords: Protein sparing effect; Hepatic steatosis; Fish health; Hematology; Intensive system; Economic analysis